Random fixed point theorems for nonexpansive and contractive-type random operators on Banach spaces. (1994) - Beg, Ismat; Shahzad, Naseer
Abstract : The existence of random fixed points. for nonexpansive and pseudocontractive random multivalued operators defined on unbounded subsets of a Banach space is proved. A random coincidence point theorem for a pair of compatible random multivalued operators is established.